Work ethics and its impact on enhancing the organizational commitment among employees in organizations. "Case Study - Technical Colleges in Jazan" - Ibrahim Shaa eldeen, Fath elrahman Taj eldeen (Technium Business and Management, 2025)
This study aimed at revealing the level of application of work ethics among employees of technical colleges in Jazan region, identifying the level of organizational commitment among employees of technical colleges in Jazan region, and revealing the impact of work ethics in enhancing organizational commitment among employees of technical colleges in Jazan region. The study relied on the descriptive analytical approach, as it is the approach that is commensurate with the achievement of the objectives of the current study. The study population may be employees of the technical colleges in Jazan region. The study tool was represented in the questionnaire, where the researcher distributed the study tool electronically to the members of the study community. He responded to the distribution process (177) employees of the technical colleges in Jazan region. The results of the study showed that the study members agreed on the work ethics of the employees of the technical colleges in Jazan region, as it came after integrity in the first rank and after mastery in the second rank and after justice in the third rank, and after cooperation in the last rank. The results of the study also showed that there is agreement among the study members on the level of organizational commitment among the employees of the technical colleges in Jazan region, and this confirms that the level of organizational commitment among the employees of the technical colleges in Jazan region came to a high degree. The results also showed a relationship between work ethics in its dimensions (integrity – mastery – justice – cooperation) and enhancing organizational commitment among the employees of the technical colleges in Jazan region.